Answer:
The Answer is: y = 2/3x - 2/3
Step-by-step explanation:
Given points: (4, 2) and (-2, -2)
Find the slope m:
m = y - y1 / (x - x1)
m = 2 - (-2) / (4 - (-2))
m = 2 + 2 / (4 + 2)
m = 4 / 6 = 2/3
Use the point slope form, substitute the point (4, 2) and solve for y to get the point slope form:
y - y1 = m(x - x1)
y - 2 = 2/3(x - 4)
y - 2 = 2/3x - 8/3
y = 2/3x - 8/3 + 6/3
y = 2/3x - 2/3
Proof:
f(-2) = 2/3(-2) - 2/3
= -4/3 - 2/3 = -6/3 = -2, giving (-2, -2)
Hope this helps!! Have an Awesome Day!! :-)